BUILDING AND STRUCTURE SAFETY ISSUES - Abror Anvarovich Kasimov (Western European Studies, 2025)
In the article, the development of the level of effective use of capital construction, construction structures in the greater hajm, which is currently being implemented, has stimulated a very rapid acceleration – the continuous improvement of the types of structures and the hom objects made from them. Therefore, the methods of their calculation, design and restoration are also improving.
Keywords: buildings; civil buildings; structures; engineering structures